2022
DOI: 10.1002/ldr.4274
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis revealed modulations of carbon and nitrogen by arbuscular mycorrhizal fungi associated with the halophyte Suaeda salsa in a moderately saline environment

Abstract: Halophytes can grow well in moderately salty habitats that restrain most plant growth. Arbuscular mycorrhizal fungi (AMF) can assist its host plants to effectively mitigate salinity stress. However, less information is available on the molecular mechanisms of AMF related to halophytes in adapting to moderate saline environments. A pot experiment was undertaken to detect the effects of AMF on the carbon (C), nitrogen (N) and phosphorus (P) concentrations in the halophyte Suaeda salsa which was grown at 100 mM N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Mycorrhizal plants often exhibit higher nitrogen fixation capacity. Differential protein expressions in AMF under salt stress were significantly associated with nitrogen metabolism [ 52 ]. In our study, primary root inoculation with AMF under high salinity resulted in increased plant nitrogen and phosphorus concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal plants often exhibit higher nitrogen fixation capacity. Differential protein expressions in AMF under salt stress were significantly associated with nitrogen metabolism [ 52 ]. In our study, primary root inoculation with AMF under high salinity resulted in increased plant nitrogen and phosphorus concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…australis and S. salsa are the predominant mycorrhizal plants that dominate the vegetation of most salt marshes. , The formation of symbiotic relationships between the roots of these plants and AM fungi results in the production of GRSP, which could contribute to SOM in coastal soils. The Duliujian River is the primary water supply to two key biological environment protection areas, the Beidagang Wetland Nature Reserve and the Tuanbo Birds and Nature Reserve .…”
Section: Methodsmentioning
confidence: 99%
“…Proteome profiling of field soil supplied with B. subtilis CP4 and Arbuscular mycorrhizal fungi (AMF) microbial consortia divulged the promotion of differentially abundant proteins (DAP) including histones, glutenin, avenin, and ATP synthase in abiotic stressed wheat, resulting in better yield and biofortification ( Yadav et al., 2022 ). An integrated proteomics and transcriptomics study successfully identified 64 DAP participating in “carbon fixation in photosynthetic organisms” as well as few amino acid metabolism pathways that may be related to C and N allocations and AMF-mediated Suaeda salsa adaptation in moderate saline conditions (100 mM NaCl) ( Diao et al., 2022 ). Similarly, proteomics data demonstrated that treatment of wheat seedlings with Bacillus sp.…”
Section: Molecular Alterationsmentioning
confidence: 99%